2014
DOI: 10.1260/0144-5987.32.5.873
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Geological Implication of Rare Earth Elements and Yttrium in Coals from the Suhaitu Mine, Wuda Coalfield, Northern China

Abstract: Inductively coupled plasma mass spectrometry (ICP-MS) was used to determine the concentrations of rare earth elements and yttrium (REY) in coal and associated rock samples from the Suhaitu Mine, Wuda Coalfield, Northern China. The concentration of REY in the No. 15 coal of the Suhaitu Mine is lower than that in normal Chinese coal, but is slightly higher than that in normal world hard coal. The roof and some partings of the No. 15 coal have been leached by ground water. The geochemical patterns of REY indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Samples collected from the Xilaifeng and Damo power plants are investigated in the present study, and the feed coals for both power plants are originally from the Suhaitu, Huangbaici, and Wuhushan mines. The mineralogy and elemental geochemistry of the coals from the Wuda Coalfield have been previously studied [26]. The power-generating capacity of the Xilaifeng Power Plant is 2.2 billion kW•h per year (2 × 200 MW generator set for the first-stage construction).…”
Section: Wuda Coalfield and The Xilaifeng And Damo Power Plantsmentioning
confidence: 99%
“…Samples collected from the Xilaifeng and Damo power plants are investigated in the present study, and the feed coals for both power plants are originally from the Suhaitu, Huangbaici, and Wuhushan mines. The mineralogy and elemental geochemistry of the coals from the Wuda Coalfield have been previously studied [26]. The power-generating capacity of the Xilaifeng Power Plant is 2.2 billion kW•h per year (2 × 200 MW generator set for the first-stage construction).…”
Section: Wuda Coalfield and The Xilaifeng And Damo Power Plantsmentioning
confidence: 99%
“…Most of these studies focused on the anomalous concentration of trace elements in coals and the affinity of these elements to the organic matters or the inorganic parts can be discerned on the level of mineral (Chu et al, 2015;Kang et al, 2014). However, the studies on the enrichment mechanisms and the origin of these elements in coals are scared (Qin et al, 2015b) and badly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a variety of trace elements including Li, Ge, U, Hg is reported to be enriched in coal seams worldwide (Dai et al., 2014; Qin et al., 2015a, 2015b; Seredin et al., 2013; Sun, 2015; Sun et al., 2012, 2013a, 2013b, 2016). Most of these studies focused on the anomalous concentration of trace elements in coals and the affinity of these elements to the organic matters or the inorganic parts can be discerned on the level of mineral (Chu et al., 2015; Kang et al., 2014). However, the studies on the enrichment mechanisms and the origin of these elements in coals are scared (Qin et al., 2015b) and badly needed.…”
Section: Introductionmentioning
confidence: 99%
“…For the coal in this research, the correlation coefficients between individual REE and ash yields were found to decline gradually from La to Lu (Figure 7), and the LREE/HREE is lower in light fractions (average at 3.29 for density from <1.60 g/cm 3 ) while much higher in heavy fractions (average at 4.29 for density >1.60 g/cm 3 ) ( Table 3), showing that LREE are more likely to be associated with inorganic matters. In other words, HREE have a stronger organic affinity than that of LREE [28,30,31]. Eskenazy [32,33] proposed that the formation of organometallic compounds by sorption on the coagulating humic and fulvic might be the bound mechanism for REE and organic matters in coal.…”
Section: Organic Affinities Of Trace Elementsmentioning
confidence: 99%